George Washington Carver : BOTANIST AND INVENTOR - Boone, Mary, 1963-; Butzer, Anna; Nuytten, Bobbie (North Mankato, Minnesota : CAPSTONE PRESS, 2018)
George Washington Carver wasn't just an inventor. He was also a botanist, a farmer, and a professor. Young readers will discover how this teacher not only improved the way people farmed, but introduced the world to more than 300 uses for the peanut.
Includes index.
Bibliography : page 23
Interest age level: Ages 6-9.
Keywords: Carver, George Washington, -- Juvenile literature -- 1864?-1943; Agriculturists -- Juvenile literature -- Biography -- United States; Botanists -- Juvenile literature -- Biography -- United States; Inventors -- Juvenile literature